Find the best solutions to your questions at Westonci.ca, the premier Q&A platform with a community of knowledgeable experts. Join our Q&A platform and get accurate answers to all your questions from professionals across multiple disciplines. Join our platform to connect with experts ready to provide precise answers to your questions in different areas.

Which equation is the inverse of [tex]\(2(x-2)^2=8(7+y)\)[/tex]?

A. [tex]\(-2(x-2)^2=-8(7+y)\)[/tex]
B. [tex]\(y=\frac{1}{4} x^2-x-6\)[/tex]
C. [tex]\(y=-2 \pm \sqrt{28+4 x}\)[/tex]
D. [tex]\(y=2 \pm \sqrt{28+4 x}\)[/tex]


Sagot :

To find the inverse of the given equation [tex]\( 2(x - 2)^2 = 8(7 + y) \)[/tex], we'll follow these steps:

1. Start with the original equation:
[tex]\[ 2(x - 2)^2 = 8(7 + y) \][/tex]

2. Divide both sides by 2 to simplify:
[tex]\[ (x - 2)^2 = 4(7 + y) \][/tex]

3. Isolate the term containing y by taking the square root of both sides:
[tex]\[ x - 2 = \pm 2\sqrt{7 + y} \][/tex]

4. Solve for [tex]\( y \)[/tex] by isolating it:
[tex]\[ \frac{x - 2}{2} = \pm \sqrt{7 + y} \][/tex]

5. Square both sides to eliminate the square root:
[tex]\[ \left( \frac{x - 2}{2} \right)^2 = 7 + y \][/tex]

6. Simplify the squared term on the left side:
[tex]\[ \frac{(x - 2)^2}{4} = 7 + y \][/tex]

7. Isolate [tex]\( y \)[/tex] by subtracting 7 from both sides:
[tex]\[ y = \frac{(x - 2)^2}{4} - 7 \][/tex]

Thus, the inverse equation is:
[tex]\[ y = \frac{(x - 2)^2}{4} - 7 \][/tex]

So, the correct inverse equation from the given options is:
[tex]\[ y = \frac{(x - 2)^2}{4} - 7 \][/tex]